Recent Application of Zebrafish Models in Atherosclerosis Research - Tang, Dandan; Geng, Fang; Yu, Chunxiao; Zhang, Ruilin (Frontiers in Cell and Developmental Biology, 2021)
Atherosclerotic cardiovascular disease is one of the leading causes of death worldwide. Establishing animal models of atherosclerosis is of great benefit for studying its complicated pathogenesis and screening and evaluating related drugs. Although researchers have generated a variety of models for atherosclerosis study in rabbits, mice and rats, the limitations of these models make it difficult to monitor the development of atherosclerosis, and these models are unsuitable for large scale screening of potential therapeutic targets. On the contrast, zebrafish can fulfill these purposes thanks to their fecundity, rapid development ex utero, embryonic transparency, and conserved lipid metabolism process. Thus, zebrafish have become a popular alternative animal model for atherosclerosis research. In this mini review, we summarize different zebrafish models used to study atherosclerosis, focusing on the latest applications of these models to the dynamic monitoring of atherosclerosis progression, mechanistic study of therapeutic intervention and drug screening, and assessment of the impacts of other risk factors.